PELATIHAN APLIKASI SPEECHACE UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS BAGI GURU - Riandini, Dini; Marlita, Reva; Romadoni, Nova Salma; Subarkah, Pungkas (Jurnal Abdi Nusa, 2024)
English language skills must be improved, especially for educators or teachers. This is especially problematic for madrasah teachers who are not English graduates. For this reason, speechace application training is needed to improve English language skills for teachers of MI Muhammadiyah, Kedungwuluh, Patikraja, Banyumas. The purpose of the course is to provide knowledge and skills for teachers in optimizing information technology, especially the speechace application to support the improvement of English language skills and abilities in the school environment. The implementation method used is the Community Language Learning (CLL) method which consists of the preparation stage, implementation stage and evaluation stage. The results of this service during the training were active participant participation and the results obtained with the pre-test and post-test pre-test and post-test, then out of 21 participants, 95% of the participants This activity is expected to contribute to efforts to improve English language skills among teachers.